2021
DOI: 10.1002/er.7301
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding and renewable energy development: What does the data say?

Abstract: Summary For the first time, this paper investigates the relationship between crowdfunding and renewable energy generation for a panel of 32 countries from 2013 to 2018. Applying the instrumental variable generalised method of moment, this study indicated that crowdfunding has a significant positive effect on renewable energy generation. Notably, 1% increase in crowdfunding raises renewable energy generation by 0.35%. Specifically, we also found that crowdfunding spurs the generation of solar energy (0.45%), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
1
17
1
Order By: Relevance
“…Recently, Alsaleh et al, 76 Alsaleh and Abdul-Rahim, 77 Alsaleh et al, 78 and Alsaleh M and Abdul-Rahim 79 have demonstrated how biomass and hydropower energy technologies can be promoted. Appiah-Otoo et al 40 have also shown how crowdfunding can be used as an alternative source of finance to fund renewable energy technologies. Waqas et al 80 and Farooq et al 81,82 have also espoused how nanofluids can be applied in cooling jet engines, thus helping combat excessive energy consumption.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Alsaleh et al, 76 Alsaleh and Abdul-Rahim, 77 Alsaleh et al, 78 and Alsaleh M and Abdul-Rahim 79 have demonstrated how biomass and hydropower energy technologies can be promoted. Appiah-Otoo et al 40 have also shown how crowdfunding can be used as an alternative source of finance to fund renewable energy technologies. Waqas et al 80 and Farooq et al 81,82 have also espoused how nanofluids can be applied in cooling jet engines, thus helping combat excessive energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…These models produce efficient outcomes since they address the issues of endogeneity, omitted variables, and cross-sectional dependence. 40,41 Finally, this research provides policy ramifications to help achieve SDG 13 and combat CC.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Appiah-Otoo I. et al [38] explore the relationship between crowdfunding and RE generation for 32 national economies from 2013 to 2018 without considering the regional level. The authors estimate crowdfunding influence on energy generation from different RE sources.…”
Section: Literature Reviewmentioning
confidence: 99%